Pathogenetic Link of Cardiac Rupture and Left Ventricular Thrombus Following Acute Myocardial Infarction: A Joint Preclinical and Clinical Study - Ma, Shan; Bai, Ling; Liu, Ping; She, Gang; Deng, Xiu-Ling; Song, An-Qi; Du, Xiao-Jun; Lu, Qun (Frontiers in Cardiovascular Medicine, 2022)
Background: Cardiac rupture (CR) and left ventricular thrombus (LVT) remain as important complications of acute myocardial infarction (MI). We explored potential pathogenetic link between CR and LVT currently regarded as independent events. Methods: Acute MI was induced in 129SV mice, onset of CR was monitored, and hearts of mice with or without fatal CR were examined histologically. From patients admitted due to acute MI during 2015–2020, data of CR or LVT patients were retrospectively collected and compared with uncomplicated patients (control). Results: 75% of mice (n=65) with MI developed CR during 2-4 days post-MI. Histological examination of CR hearts revealed common presence, in the rupture tunnel, of platelet-rich intra-mural thrombus that connected at the endocardial site to platelet-fibrin thrombi within LVT. In CR or non-CR mouse hearts, LV blood clot often contained a portion of platelet-fibrin thrombus through which the clot adhered to the infarct wall. In non-CR hearts, sites of incomplete CR or erosion of infarct wall were typically coated with platelet thrombus and dense inflammatory cells. Of 8,936 patients with acute MI, CR and LVT occurred in 102 (1.14%) and 130 (1.45%) patients, respectively, with 3 cases had both complications. CR accounted for 32.8% of in-hospital deaths. Majority of CR (90%) or LVT (63%, LVT-early) occurred within 7 days. Patients of CR and LVT-early had higher levels of inflammatory cell counts and cardiac injury biomarkers versus control and LVT-late groups. Conclusion: CR and LVT post-MI remain significant clinical challenge. LVT that occurs early post-MI might be initiated by thrombo-inflammation following endocardial CR or erosion.